Latin American smart cities: Between worlding infatuation and crawling provincialising. (February 2021) - Irazábal, Clara; Jirón, Paola
Smart city initiatives in Latin America aim to harness information and communication technologies to make urban service provision and management more efficient, transparent and user-friendly. Latin American cities have been relatively slow to adopt such initiatives, but there is inter- and intra-urban variety in the region. We offer illustrative vignettes of Rio de Janeiro, Santiago and Medellín, which have experimented with different formats for smart city programme design, implementation and management. While top-down and flashier smart city projects in these cities reflect worlding aspirations on the part of urban elites, mixed and bottom-up approaches serve to provincialise and often informalise the initiatives in manners that destabilise elitism and more equitably distribute costs and benefits. One of the biggest challenges these cities share in developing smarter initiatives is inequality, given that most interventions are located in or benefit higher-income areas and actors. As instruments to provincialise the discourses and practices of smart cityness in the region, we propose that cities adopt the '6-Es smart cities framework' (efficiency, economy, ecology, equity, education and engagement) and mobilise public–private– people partnerships within city plans and implementation processes.